2012
DOI: 10.1007/s00253-012-4377-5
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for strain improvement in Fusarium fujikuroi: overexpression and localization of key enzymes of the isoprenoid pathway and their impact on gibberellin biosynthesis

Abstract: The rice pathogen Fusarium fujikuroi is known to produce a wide range of secondary metabolites, such as the pigments bikaverin and fusarubins, the mycotoxins fusarins and fusaric acid, and the phytohormones gibberellic acids (GAs), which are applied as plant growth regulators in agri- and horticulture. The development of high-producing strains is a prerequisite for the efficient biotechnological production of GAs. In this work, we used different molecular approaches for strain improvement to directly affect ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 89 publications
(81 reference statements)
0
25
0
Order By: Relevance
“…However, changes in an available acetyl‐CoA pool are not necessarily linked to an altered production rate of certain SMs due to the presence of other limiting factors. One such example is the negative feedback loop of the 3‐hydroxy‐3‐methyl‐glutaryl‐CoA reductase (HmgR) in the isoprenoid pathway: overexpression of HMGR resulted in decreased instead of elevated GA levels in F. fujikuroi (Albermann et al ., ). In addition, other global regulators, such as the velvet protein FfVel1 which negatively affects BIK biosynthesis, might overrule the activating effect of FfSge1 on this metabolite.…”
Section: Discussionmentioning
confidence: 97%
“…However, changes in an available acetyl‐CoA pool are not necessarily linked to an altered production rate of certain SMs due to the presence of other limiting factors. One such example is the negative feedback loop of the 3‐hydroxy‐3‐methyl‐glutaryl‐CoA reductase (HmgR) in the isoprenoid pathway: overexpression of HMGR resulted in decreased instead of elevated GA levels in F. fujikuroi (Albermann et al ., ). In addition, other global regulators, such as the velvet protein FfVel1 which negatively affects BIK biosynthesis, might overrule the activating effect of FfSge1 on this metabolite.…”
Section: Discussionmentioning
confidence: 97%
“…Another biosynthetic pathway with enzymes localized to the cytosol is the diterpenoid phytohormone, gibberellin, produced by Fusarium fujikuroi (see section 3.2.3 for more details). In gibberellin biosynthesis, ent -copalyldiphosphate/ ent -kaurene synthase (Cps/Ks), a middle-pathway bifunctional enzyme that catalyzes conversion of geranylgeranyl diphosphate (GGDP) to ent -kaurene is found to localize to the cytosol 50 . It may be noteworthy that unlike the peroxisomes that can either house the initial or terminal biosynthetic step(s) of a pathway, the cytosol as of to date, is reported to only house intermediate steps of a biosynthetic pathway.…”
Section: Reaching the Right Location: Tracking Natural Products Symentioning
confidence: 99%
“…A reductase (HmgR), in rice pathogen Fusarium fujikuroi (Albermann et al, 2013). Wang et al (2013) reported that the specific yield of ent-kaurene was enhanced by assembling and modulating the efflux pumps such as the AcrB and TolC components in E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Albermann et al (2013) have shown that GA production was elevated by overexpression of the GA pathway genes, geranylgeranyl diphosphate synthase 2 (ggs2) and bifunctional entcopalyldiphosphate synthase/ent-kaurene synthase (cps/ks), and truncation of the key enzyme of the mevalonate pathway, hydroxymethylglutaryl coenzyme. A reductase (HmgR), in rice pathogen Fusarium fujikuroi (Albermann et al, 2013).…”
Section: Introductionmentioning
confidence: 99%